An Evaluation Framework for New ICTs Adoption in Architectural Education - Franklyn Chukwunonso; Michael. C Oguike (Institute of Advanced Engineering and Science, 2013)
The advent of new Information and Communication Technologies (ICTs) poses several challenges for its use and adoption particularly for teaching and learning purposes in most Higher Educational Institutions (HEIs). Understanding the criteria to use and how to measure success are some of the challenges faces by most departments of Architecture in Nigerian Universities. Thus, this paper has attempted to address these challenges by proposing an evaluation framework for the adoption of new ICTs in tertiary institutions of learning with particular interest in Architectural education. Baseline information collected from the department of architecture in five different Nigerian Universities was used to identify the major constraints encountered in Information and Communication Technologies adoption in Architectural education and the best approach that will promote better rate of Information Technology (IT) adoption. The major contribution of the study is that the proposed framework can be used to interpret specific results as to whether the use of technology within a particular literacy program led to improved learning, and provide a better understanding of such results in larger contexts and various aspects of other issues related to evaluation, access, and literacy learning in Architectural education.DOI: http://dx.doi.org/10.11591/ij-ict.v2i3.5285